2011
DOI: 10.1038/nature09760
|View full text |Cite
|
Sign up to set email alerts
|

A closely packed system of low-mass, low-density planets transiting Kepler-11

Abstract: When an extrasolar planet passes in front of (transits) its star, its radius can be measured from the decrease in starlight and its orbital period from the time between transits. Multiple planets transiting the same star reveal much more: period ratios determine stability and dynamics, mutual gravitational interactions reflect planet masses and orbital shapes, and the fraction of transiting planets observed as multiples has implications for the planarity of planetary systems. But few stars have more than one k… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
457
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 576 publications
(475 citation statements)
references
References 42 publications
15
457
2
1
Order By: Relevance
“…On the other hand, the atmosphere of planets on such short orbit (days) may have been evaporated by the star, contrary to planets on wider orbits. KEPLER discoveries of small planets on longer-period orbit (Lissauer et al 2011) have indeed shown that their average density is generally lower than in the previously mentioned cases. One possible explanation is that they may have at least kept a thick gaseous envelope.…”
Section: Nature Of Found Planetsmentioning
confidence: 99%
“…On the other hand, the atmosphere of planets on such short orbit (days) may have been evaporated by the star, contrary to planets on wider orbits. KEPLER discoveries of small planets on longer-period orbit (Lissauer et al 2011) have indeed shown that their average density is generally lower than in the previously mentioned cases. One possible explanation is that they may have at least kept a thick gaseous envelope.…”
Section: Nature Of Found Planetsmentioning
confidence: 99%
“…Kepler-11, an extremely compact system of 6 transiting planets, was discovered with 5 of the 6 planets exhibiting TTVs so that their masses could be estimated directly from the Kepler data. 39 The planetary orbits in this system are highly coplanar.…”
Section: Key Science Resultsmentioning
confidence: 94%
“…We have no information about their composition, but models suggest that they could exhibit silicate compounds in the gaseous/liquid phase (Léger et al 2011, Valencia et al 2010Rouan et al 2011). At lower temperatures (700-1000 K), as in the case of Kepler 11b, f (Lissauer et al 2011) and Kepler 20b, c, e, f (Gautier et al 2012), silicates do not evaporate.…”
Section: Hot and Warm Small Exosmentioning
confidence: 99%